Examining the Role of Business Architecture Practices in Digital Transformation Outcomes - O'Higgins, Dennis James (Digital Repository of Theses - SSBM Geneva, 2025)
This research explores the role of Business Architecture (BA) as a critical enabler of Digital Transformation (DT) success, addressing a significant challenge faced by organisations today: aligning digital initiatives with strategic goals. Despite considerable investments in DT, many organisations fail to realise expected benefits due to disconnects between digital efforts and organisational objectives. BA provides a structured approach to harmonize business strategy with operational capabilities, potentially bridging these gaps. The study adopts a sequential explanatory mixed-methods design, combining quantitative data from a survey of 129 BA practitioners and organisational leaders with qualitative insights from two focus groups involving 25 participants. In the quantitative phase, Structural Equation Modelling (SEM) assesses the relationships between BA practices, DT outcomes, and organisational factors, focusing on constructs such as strategic alignment, operational efficiency, and service delivery. The qualitative phase complements these findings by delving into practitioners’ experiences, providing context and depth to the observed quantitative trends. Results from SEM reveal that BA practices significantly enhance DT outcomes, particularly through fostering alignment between DT initiatives and strategic goals, improving operational efficiency, and supporting robust service delivery. Organisations with mature BA practices show stronger alignment between their digital strategies and overall objectives, yielding performance gains and a competitive edge. The focus group discussions underscore the importance of leadership support, cross-functional collaboration, and a change-embracing culture as essential enablers for effective BA implementation in DT. This study makes contributions to both academic literature and practitioner knowledge by empirically validating BA’s role in DT. The research highlights actionable insights for organisations aiming to leverage BA for successful digital transformation, emphasizing the need for strategic alignment, strong leadership, and a culture that supports continuous adaptation to change. These findings offer a pathway for organisations seeking sustainable competitive advantages in the evolving digital landscape.